Rock art and identity in the north eastern Cape province - Mallen, Lara (My University, 2009)
A new and unusual corpus of rock art, labelled as Type 3 imagery, forms the focal point of this dissertation. Type 3 art is found at twelve known sites within the region once known and Nomansland, in the south-eastern mountains of South Africa. It is significant because it differs from the three major southern African rock art traditions, those of San, Khoekhoen and Bantu-speakers in terms of subject matter, manner of depiction and use of pigment. The presence of Type 3 art in Nomansland raises questions about its authorship, its relationship to the other rock art of the area, and the reasons for its production and consumption, which I consider in this dissertation. I argue that this corpus of art was made in the late nineteenth century, probably by a small, multi-ethnic stock raiding band. I consider the inception of this rock painting tradition, and the role of the art in the contestation and maintenance of identity.
Keywords: rock art; Identity; North eastern Cape